DAKWAHTAIMENT “EXISTENCE OF DAKWAH IN THE TELEVISION INDUSTRY IN INDONESIA: THE FIGHT BETWEEN SYIAR AND MARKET SEGMENTATION - Mhd. Syahirul A. Rambe; Haris Muda Panasean Lubis; Mailin Mailin (Universitas Dharmawangsa, 2021)
ABSTRACTThe advantages of industrial technology have achieved unprecedented efficiency, so that they are able to produce information, communication and transportation tools so cheaply and in such a short time. Too much freedom. One of the products of this transformation is the proliferation of these da'wahtainment programs which essentially combine